High‐resolution melting and immunohistochemical analysis efficiently detects mutually exclusive genetic alterations of adamantinomatous and papillary craniopharyngiomas. Issue 1 (25th August 2017) - Yoshimoto, Koji; Hatae, Ryusuke; Suzuki, Satoshi O.; Hata, Nobuhiro; Kuga, Daisuke; Akagi, Yojiro; Amemiya, Takeo; Sangatsuda, Yuhei; Mukae, Nobutaka; Mizoguchi, Masahiro; Iwaki, Toru; Iihara, Koji
Abstract : Craniopharyngioma consists of adamantinomatous and papillary subtypes. Recent genetic analysis has demonstrated that the two subtypes are different, not only in clinicopathological features, but also in molecular oncogenesis. Papillary craniopharyngioma (pCP) is characterized by a BRAF mutation, the V600E (Val 600 Glu) mutation. Adamantinomatous craniopharyngioma (aCP) can be distinguished by frequent β‐catenin gene ( CTNNB1 ) mutations. Although these genetic alterations can be a diagnostic molecular marker, the precise frequency of these mutations in clinical specimens remains unknown. In this study, we first evaluated BRAF V600E and CTNNB1 mutations in four and 14 cases of pCP and aCP, respectively, using high‐resolution melting analysis followed by Sanger sequencing. The results showed that 100% (4/4) of pCP cases had BRAF V600E mutations, while 78% (11/14) of the aCP cases had CTNNB1 mutations, with these genetic alterations being subtype‐specific and mutually exclusive. Second, we evaluated BRAF V600E and CTNNB1 mutations by immunohistochemical analysis (IHC). All pCP cases showed positive cytoplasmic staining with the BRAF V600E‐mutant antibody (VE‐1), whereas 86% (12/14) of aCP cases showed positive cytoplasmic and nuclear staining for CTNNB1, suggesting a CTNNB1 mutation. Only one case of wild‐type CTNNB1 on the DNA analysis showed immunopositivity on IHC. We did not detect a coexistence of BRAF V600E and CTNNB1 mutations in any single tumor, which indicated that these genetic alterations were mutually exclusive. We also report our modified IHC protocol for VE‐1 staining, and present the possibility that BRAF V600E mutations can be used as a diagnostic marker of pCP in the differentiation of Rathke cleft cyst with squamous metaplasia.